1994
DOI: 10.1007/bf00173415
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equilibrium between insertion and excision of P elements in highly inbred lines from an M? strain of Drosophila melanogaster

Abstract: Six highly inbred lines of Drosophila melanogaster extracted from an M' strain (in the P/M system of hybrid dysgenesis) were studied for the evolution of the number and chromosomal location of complete and defective P elements through generations 52-200. These lines possessed full-sized P elements but differed in their cytotype (M or P). Three lines with P cytotype and full-sized P elements at site 1A had a constant P copy number over generations with low rates of insertion and excision. Three lines with M cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
4
16
0
1
Order By: Relevance
“…Here, we observed replicative transposition rates ranging from 0.3-0.5 per copy and per generation during the very early stages of the invasion and 0.01-0.03 for the 50 subsequent generations. These figures are of the same order of magnitude as for active P elements during hybrid-dysgenesis stages recorded in the laboratory (35), although dysgenic symptoms were never observed for mariner.…”
Section: Discussionsupporting
confidence: 66%
“…Here, we observed replicative transposition rates ranging from 0.3-0.5 per copy and per generation during the very early stages of the invasion and 0.01-0.03 for the 50 subsequent generations. These figures are of the same order of magnitude as for active P elements during hybrid-dysgenesis stages recorded in the laboratory (35), although dysgenic symptoms were never observed for mariner.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies of D. melanogaster report transposition rates ranging from 10 -5 to 10 -3 events/copy/generation under normal conditions for retroelements (Charlesworth et al, 1992;Nuzhdin and Mackay, 1995;Suh et al, 1995;Maside et al, 2000), about 10 -2 after heat shocks (Vasilyeva et al, 1999) and up to 10 -1 in dysgenic crosses (Seleme et al, 1999). The same orders of magnitude are reported for Class II elements, in normal and dysgenic conditions (Eggleston et al, 1988;Biémont, 1994). Although they remain exceptional and hardly quantifiable events, excisions seem to occur more frequently for Class II elements.…”
Section: Transposition Ratesupporting
confidence: 56%
“…Thus, P-element insertions residing in cluster 20A could account for zygotic repression in some Q strains. However, P-element insertions in cytological position 20A, which harbors cluster 20A, are relatively rare in natural populations (Ronsseray et al 1989b;Biémont 1994), which is inconsistent with the reported prevalence of zygotic P-element repression (Jackson et al 1988).…”
Section: Repressor Proteins or Pirnas?mentioning
confidence: 92%